Superwettable Surface Engineering in Controlling Cell Adhesion for Emerging Bioapplications. Issue 12 (13th September 2020) - Cui, Haijun; Wang, Wenshuo; Shi, Lianxin; Song, Wenlong; Wang, Shutao
Abstract: The dynamic liquid environment of live cells makes it necessary to consider the surface wettability when designing biomaterials and related devices. Especially superwettability, as the extreme state of wettability, has become a unique platform for regulating cell behaviors elaborately including adhesion, spreading, proliferation, differentiation, and apoptosis, which elicits the promising applications on biomedicine and advanced biodevices. In this review, the controlling cell adhesion on superwettable engineering surfaces is summarized. Next, the related bioapplications utilizing the surface superwettability are recapitulated, including reversible surface wettability for cell capture/adhesion, superwettability‐based patterns for cell arrays/aggregations construction, superwettability for antiplatelet adhesion, and superwettable surfaces as antimicrobial materials. Several design concepts are concluded on the emerging bioapplications of superwettable surface. Although so many efforts have been made for revealing the mechanism of cell functions on the superwettable surface, the complexity and variability between superwettable surface and liquid environment in physiological activities of organisms still requires impeccable theories, and the remaining unclear mechanisms of superwettability for biological systems are also discussed. As an outlook, the surface superwettability is just beginning to demonstrate its great potential in biology, offering great opportunities in tissue engineering, implantable devices, biosensors, drug‐screening, and cancer diagnostics. Abstract : Surface superwettability is a unique property of materials endowed by nature. Surface wettability provides crucial guidance in surface engineering of solid or soft materials. The emerging bioapplications on surface superwettability are summarized, including cell adhesion, cancer cell capture, cell sheet harvest, cell arrays or aggregations construction, antiplatelet, and antibacteria.